Design of wideband continuous class-F power amplifier using low pass matching technique and harmonic tuning network - Sadeque, Md. Golam; Yusoff, Zubaida; Hashim, Shaiful Jahari; Mohd Marzuki, Azah Syafiah; Lees, Jonathan; Fitzpatrick, Dominic (IEEE, 2022)
Many countries have allocated new frequency bands for fifth generation (5G) communication systems. In this paper, a wideband continuous class-F (CCF) radio frequency power amplifier (RFPA) is presented for the new 5G frequency band, from 3.3 GHz to 4.3 GHz using a 10 W Cree CGH40100F device. A unique wideband RFPA design approach for the output matching network (OMN) is also presented by applying a harmonic tuning network (HTN) for the harmonics and a low pass matching technique (LPMT) for the fundamental frequency. The RFPA is fabricated, and promising measurement results show a drain efficiency of 55.9% to 65.3% is achieved at an output power of 40 dBm (± 0.3 dBm) over a frequency range of 3.3 GHz to 4.3 GHz. A two-tone signal with a 10 MHz spacing was also applied to investigate the linearity of the RFPA.